Дослідження старіння мінеральних гідравлічних олив. І. Фракційний склад - Кузнєцова, Олена Яківна; Нетреба, Жанна Миколаївна (Технологічний аудит та резерви виробництва, 2015)
Досліджено особливості перебігу реакцій деструкції в молекулах бі- та трициклічних нафтенових вуглеводнів, які містяться в перших фракціях модельних зразків гідравлічної оливи «Гідронікойл FH-51», з метою встановлення механізму старіння оливи. Знайдено, що внаслідок перебігу процесів деструкції молекул вуглеводнів, дегідрування та ущільнення продуктів цих перетворень відбувається зменшення кількості низкокиплячих вуглеводнів та збільшення відповідно висококиплячих у фракційному складі гідравлічної оливи з часом роботи в гідравлічній системі повітряного судна.
Research of aging of mineral hydraulic oils. I. Fraction composition
Ukraine, as a member of the International Civil Aviation Organization, claimed responsibility for ensuring high requirements for flight safety, which constitute a set of measures, including the organization of reliable and trouble-free operation of the hydraulic system of the aircraft and its units. The working body of the hydraulic system of the aircraft is hydraulic oil, its properties depend on the efficiency and reliability of the aircraft exploitation. The ability of the oil to keep the chemical composition and performance of the limits that ensure the reliability of the hydraulic system of the aircraft determines its guaranteed resource life. In this context, the problem of research of aging process of hydraulic oil during the operation of the aircraft is relevant. During researches it is established peculiarities of degradation reactions in molecules of bicyclic and tricyclic naphthenes of first fractions of model samples of oil "Hydraunycoil FH-51", the result of which is the formation of mono- and bicyclic naphthenes. During the last dehydrogenation it is formed unstable cyclomono- and cyclodiolefine and aromatic hydrocarbons, which results in a compression during operation of the oil to decrease as the content of the first fraction of all types of naphthenic compounds and reducing output of the first and second fractions to increase the yield, respectively.
Keywords: старіння оливи; мас-спектральний аналіз; деструкція молекул вуглеводнів; гарантований ресурс придатності; oil aging; mass spectral analysis; destruction of hydrocarbon molecules; guaranteed resource life